Pengaruh Giberelin Dan MOL Bonggol Pisang Batu Terhadap Pertumbuhan Cabai Merah Besar (Capsicum annuum L.) - Istiqomah; Nurcahyani, Endang; Yulianty; Mahfut (BULLET : Jurnal Multidisiplin Ilmu, 2026)
Large red chili (capsicum annuum L.)  is a herbaceous plant that has a spicy taste and is one of the types of chili that is most widely used by the Indonesian people, especially on a household scale by 61%. Therefore, increasing the production of large red chili needs to be done, one of which is through the administration of gibberellin and Local Microorganisms (MOL) from Batu banana corms. This study aims to determine the effect of administering gibberellin (GA3) and MOL from Batu banana corms on the growth of large red chili plants, determine the most effective concentration, and observe the interaction between the two. The study was conducted from February to March 2024 at the Botany Laboratory, FMIPA, University of Lampung, using a factorial Completely Randomized Design (CRD). The first factor was gibberellin with two concentration levels (0% and 10%), and the second factor was MOL from Batu banana corms with three concentration levels (0%, 10%, and 20%) with five replications, resulting in 30 experimental units. The parameters observed included plant height, root length, fresh weight, dry weight, relative water content, chlorophyll content, and leaf visualization. Data were analyzed using ANOVA followed by a 5% Tukey test. The results showed that the combination of 10% GA3 and 20% MOL affected fresh weight, dry weight, and chlorophyll a, b, and total, while the control affected plant height, root length, and relative water content.